An Analysis of Risk Taking Behaviors of High School Students in Terms of Their Decision Making Skills and Various Factors - Murat Sinan Özkan; Selim Gündoğan; Jale Eldeleklioğlu (Elementary Education Online, 2023)
The purpose of this study is to analyze risk taking behaviour of high school students in terms of their decision making skills and other various factors. 340 students consisting of 195 girls and 145 boys participated in the research. To determine high school students’ risk taking behaviour, the “Risk Taking Scale in Adolescents” was used; to determine their decision making skills, the “Decision Strategies Scale” was used; and to determine qualitative factors the “Personal Information Form” designed by the researchers was used. For analyzing the data of the research, the t-test, Pearson Product-moment Correlation Coefficient Technique and Multiple Regression Analysis Technique were used. The findings acquired from the research were discussed in terms of their relation with the body of literature and some suggestions were given.